Development of substitutional computational methods for maximum-likelihood detection of the object’s near-zero apparent motion on the series of CCD-frames - Хламов, Сергей Васильевич; Саваневич, Вадим Евгеньевич; Брюховецкий, Александр Борисович; Орышич, Сергей Сергеевич (Technology audit and production reserves, 2016)
The objects with near-zero apparent motion during observation are the subject of study. The main disadvantage of such objects is the fact that the object’s movement on a series of CCD-frames can be compared with errors of the position determining of the object. We propose using the substitutional decision rules to detect object’s near-zero apparent motion. These rules are based on the maximum-likelihood criterion and use a joint density of the measurements distribution as maximum-likelihood function. Substitutional computation methods for maximum-likelihood detection of the object’s near-zero apparent motion on the series of CCD-frames are developed. They are based on using of maximum-likelihood criterion in the decision rules of detection. Likelihood ratio is used as criterion for a sufficient statistic with minimum amount. This ratio is compared with the critical values selected in accordance with a predetermined criterion. Using of the substitutional decision rules is justified by the absence of a priori information about likelihood function parameters such as parameters of the apparent motion of objects and dispersion of the positional measurements of series. The article describes the cases with known, unknown variance of object’s position measurements on the CCD-frames and using its external evaluation. Parameters of observed object’s apparent motion should be previously estimated for using the synthesized decision rules. Also the corresponding interpolated coordinates on the investigated frames should be determined.